Optimizing media of lactobacillus rhamnosus for lactic acid fermentation - Mel, Maizirwan; Abdul Karim, Mohd Ismail; Mohd Salleh, Mohammad Ramlan; Mohamad Amin, Noraini Alamin (Asian Network for Scientific Information, 2008)
The aim of this study was to optimize the main media components that affect the production of lactic acid by Lactobacillus rhamnosus fermentation. In the experiment,the two variables (glucose and peptone) were optimized using tbe Central Composite Design (CCD) metbod by STATISTICA Software.The optimization studies were successfully carried out in shake flask experiments. The results indicated that the optimun concentration of glucose and peptone for optimun bacterial grovvth rate and lactic acid production in shake flask were 9.80 and 9.98 g L -1, respectively. The optimwn productivity of the lactic acid was 0.630 g g-l h which correspond to optimwn grovvth rate of the bacteria at 0.341 h-1.